American dream [compact disc] - 21 Savage, 1992- (Slaughter Gang, LLC, 2024)
Nearly six years after his last solo release, 21 Savage returns with the long-awaited new studio album, American Dream. Debuting on the Billboard Top 200 chart at #1 for two weeks in a row, the set continues in the rapper's stone-faced trap tradition but adds some new elements, including RB on the track Prove It featuring Summer Walker and pop on the Doja Cat collaboration n.h.i.e. There is no lack of hip-hop prowess, though, with guest features from Metro Boomin', the Weeknd, Young Thug, Travis Scott, Lil Durk, and more.